Striking a new balance : tripartism and labour relations in post-colonial Singapore - Ho, Justin Chang Pern (2017)
Tripartism has often been recognised as the cornerstone of labour relations in Singapore and the key to its success in nation building and economic development. Nevertheless, there has been a lack of critical discussion over its structural dynamics, and its role in the development of Singapore’s industrial relations system. What were the actual relations between the different actors in the tripartite model? How have these relations and the dynamics of collaboration and consultation changed over time in the considerations of the transformation in Singapore’s economy over the last 50 years?